White tea (Camellia sinensis) inhibits proliferation of the colon cancer cell line, HT-29, activates caspases and protects DNA of normal cells against oxidative damage - Hajiaghaalipour, F.; Kanthimathi, M.S.; Sanusi, J.; Rajarajeswaran, J. (Elsevier, 2015)
Tea (Camellia sinensis) is one of the most consumed beverages in the world. White tea is made from the buds and young leaves of the tea plant which are steamed and dried, whilst undergoing minimal oxidation. The MTT assay was used to test the extract on the effect of the proliferation of the colorectal cancer cell line, HT-29. The extract inhibited the proliferation of HT-29 cells with an IC50 of 87 mu g/ml. The extract increased the levels of caspase-3, -8, and -9 activity in the cells. DNA damage in 3T3-L1 normal cells was detected by using the comet assay. The extract protected 3T3-L1 cells against H2O2-induced DNA damage. The results from this study show that white tea has antioxidant and antiproliferative effects against cancer cells, but protect normal cells against DNA damage. Regular intake of white tea can help to maintain good health and protect the body against disease. (C) 2014 The Authors. Published by Elsevier Ltd.